Correction - Anthon, Carl Thomas (2024)
When the article was published, the Result-section of the Abstract was given in a misleading wording. Instead of “Absence of acquired immune deficiency syndrome (AIDS), non-cancer-related immune deficiency, liver failure, male sex, septic shock, and bleeding at ICU admission were associated with the development of thrombocytopenia during ICU stay”. it should read “Non-AIDS-, non-cancer-related immune deficiency, liver failure, male sex, septic shock, and bleeding at ICU admission were associated with the development of thrombocytopenia during ICU stay.” The Original publication has been corrected.